2021
DOI: 10.1101/2021.03.08.434471
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A cross-cohort analysis of autosomal DNA methylation sex differences in the term placenta

Abstract: Background Human placental DNA methylation (DNAme) data is a valuable resource for studying sex differences during gestation, as DNAme profiles after delivery reflect the cumulative effects of gene expression patterns and exposures across gestation. Here, we present an analysis of sex differences in autosomal patterns of DNAme in the uncomplicated term placenta (n=343) using the Illumina 450K array. Results Using a false discovery rate < 0.05 and a mean sex difference in DNAme beta value of > 0.10, we i… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 73 publications
0
1
0
Order By: Relevance
“…Several genome wide association methylome studies (or Epigenome Wide Association Studies - EWAS) have highlighted differences in DNA methylation patterns linked to sex differences in genes on the autosomes (1720). Previous studies have reported sites showing varying methylation due to sex differences in various tissues such as saliva, placenta, brain, pancreatic islets and whole blood (17, 19, 2127). Early studies in this area did not account for cross hybridizing probes which map to both autosomal and sex chromosome loci (28, 29).…”
Section: Introductionmentioning
confidence: 99%
“…Several genome wide association methylome studies (or Epigenome Wide Association Studies - EWAS) have highlighted differences in DNA methylation patterns linked to sex differences in genes on the autosomes (1720). Previous studies have reported sites showing varying methylation due to sex differences in various tissues such as saliva, placenta, brain, pancreatic islets and whole blood (17, 19, 2127). Early studies in this area did not account for cross hybridizing probes which map to both autosomal and sex chromosome loci (28, 29).…”
Section: Introductionmentioning
confidence: 99%